Palliative care for people with neoplastic wounds: perceptions and practices of the nursing team - Michelle Souza Nascimento; Nayara Costa Farah; Adélia Dayane Guimarães Fonseca; Thaís Vasconselos Amorim; Elaine Miguel Delvivo Farão; Andyara do Carmo Pinto Coelho Paiva (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To understand the perceptions and practices of the nursing team in assisting people in palliative care with neoplastic wounds. Method: A descriptive study with a qualitative approach, carried out with 12 nursing professionals working in a Level II High Complexity Oncology Hospital, located in the interior of Minas Gerais, Brazil, in 2022. Data was collected through semi-structured interviews and analyzed according to the method proposed by Bardin. Results: Three thematic categories emerged: Nursing care that transcends the management of neoplastic wounds; The role of the nursing team in the assessment and care of neoplastic wounds; and Feelings that involve nursing professionals in the context of palliative care. Conclusion: It is essential to approach the person holistically. The management of neoplastic wounds has its own particularities, since pain is a symptom that usually accompanies the lesion, in addition to the odor and discomfort that the person and their family may feel. Palliative care is relevant to help manage the symptoms of these lesions. Workers often experience feelings such as anguish, fear, sadness and frustration.